A framework for analyzing cascading failure in large interconnected power systems: A post-contingency evolution simulator. (October 2016) - Bompard, Ettore; Estebsari, Abouzar; Huang, Tao; Fulli, Gianluca
Highlights: Cascading failures simulation, modeling automatic and human decisions. Multiple stages and strategies for accelerating post-contingency recovery. Evaluation of the damage/impact of real or simulated network failures. Scientific evidences for decision makers to allocate the limited resources for security enhancement. Abstract: The power system protection against different threats has become a key and growing concern. A materialized threat provokes a sequence of chained events and counteractions in the grid. The simulation and analysis of the cascades leading to blackouts are extremely intricate due to various time scales, multiple interacting automatic and human-driving actions, and the large set of possible countermeasures. The possibility to simulate the cascading events, considering both behaviors of the system and human/automatic actions, is crucial for designing protective strategies, guiding investments and supporting policy decision making on reinforcing the system. In this paper, we present a simulation framework which, with a steady-state approach, provides system snapshots during cascading failures, taking into account the actions for minimizing the load-shedding or maximizing the restoration of the unserved loads. The conceptual framework is implemented as a software tool to simulate system behaviors and actions like automatic countermeasures, human interventions and optimal operational strategies to defend and restore the system. Combined with a suitable economic assessment method, it can be used to evaluate investments in countermeasures and the potential costs of different threats. It has been applied to study the countermeasures to enhance the security of the EU power transmission network.